Pengembangan Modul Bimbingan Kelompok dengan Teknik Role Playing untuk Meningkatkan Empati Siswa SMP Laboratorium Universitas Negeri Malang - Ratriani Santi Dewi; Irene Maya Simon; Lutfi Fauzan; Ratriani Santi Dewi; Irene Maya Simon (Universitas Negeri Malang, 2022)
Abstract: The rapid development of the era and technology makes individuals become individuals who are increasingly indifferent to other people and the environment around them, this is also called low empathy. The purpose of this development research is to produce a product in the form of a Role Playing module Efforts to Increase Empathy for Middle School Students. The model in this study is Research and Development. development research obtained student data with an empathy scale for students, an assessment instrument for material & media experts, as well as an assessment of prospective users. The final validation of the assessment of the material expert test by 2 BK (Guidance and Counseling) lecturers, the media by 2 TEP (Educational Technology) lecturers, and prospective module users, namely 1 counselor and 2 students indicate that the module that has been developed is feasible and accepted by Laboratory Junior High School students Malang State University. Abstrak: Pesatnya perkembangan jaman dan teknologi membuat individu menjadi pribadi yang semakin acuh tau acuh dengan orang lain maupun lingkungan disekitarnya, hal tersebut disebut juga rendahnya empati. Tujuan dari penelitian pengembangan ini yaitu untuk menghasilkan sebuah produk berupa modul Role Playing Upaya Meningkatkan Empati Siswa SMP. Model dalam penelitian ini yaitu Research and Development. penelitian pengembangan memperoleh data siswa dengan skala empati untuk siswa, instrumen penilaian ahli materi & media, serta penilaian uji calon pengguna. Akhir validasi penilaian dari uji ahli materi oleh 2 dosen BK (Bimbingan dan Konseling), media oleh 2 dosen TEP (Teknologi Pendidikan), dan calon pengguna modul yaitu 1 Konselor dan 2 siswa menunjukan bahwa modul yang telah dikembangakan sudah layak dan diterima siswa SMP Laboratorium Universitas Negeri Malang.